Estado Nutricional y Rendimiento Académico en Escolares de Huamachuco - Cerna Vargas, Wilma Jacqueline (2019)
The present investigation of descriptive, correlational and cross-sectional type. It was carried out with the students of the educational institution César Vallejo de Huamachuco in the year 2018; with the purpose of determining the relationship that exists between nutritional status and level of academic performance in schoolchildren. The sample universe was constituted by 168 school children of 3rd and 4th grade of primary education. For data collection, nutritional status scale (height and weight) and academic performance (EVENRA) (ratings) were used. The results are presented in simple and double-entry statistical tables, and to measure the relationship between variables the test of independence of Chi square criteria was used, observing that there is a (11.9 porcent) with problems in the nutritional status, as well as not There is a statistical relationship between the study variables in the students who participated in the study.